2017
DOI: 10.1038/s41598-017-08642-2
|View full text |Cite
|
Sign up to set email alerts
|

Spray-cast multilayer perovskite solar cells with an active-area of 1.5 cm2

Abstract: We utilise spray-coating under ambient conditions to sequentially deposit compact-TiO2, mesoporous-TiO2, CH3NH3PbI(3−x)Clx perovskite and doped spiro-OMeTAD layers, creating a mesoporous standard architecture perovskite solar cell (PSC). The devices created had an average power conversion efficiency (PCE) of 9.2% and a peak PCE of 10.2%; values that compare favourably with control-devices fabricated by spin-casting that had an average efficiency of 11.4%. We show that our process can be used to create devices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
91
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 45 publications
0
91
1
Order By: Relevance
“…As a result, PCEs up to 17.8% were demonstrated for PSCs. Several studies have already demonstrated this, for instance, spray coating of PEDOT:PSS, [107] CuSCN, [108] Spiro-OMeTAD, [109] compact TiO 2 , [8,109] mesoporous TiO 2 , [109] and PCBM. [31] The study showed the significance of utilizing different boiling point solvents in various ratios to control the evaporation of solvents, but also relied on substrate heating at 120 °C.…”
Section: Spray Coatingmentioning
confidence: 98%
See 4 more Smart Citations
“…As a result, PCEs up to 17.8% were demonstrated for PSCs. Several studies have already demonstrated this, for instance, spray coating of PEDOT:PSS, [107] CuSCN, [108] Spiro-OMeTAD, [109] compact TiO 2 , [8,109] mesoporous TiO 2 , [109] and PCBM. [31] The study showed the significance of utilizing different boiling point solvents in various ratios to control the evaporation of solvents, but also relied on substrate heating at 120 °C.…”
Section: Spray Coatingmentioning
confidence: 98%
“…[31] The study showed the significance of utilizing different boiling point solvents in various ratios to control the evaporation of solvents, but also relied on substrate heating at 120 °C. [109,110] Mohamad et al used PEDOT:PSS and PCBM as their HTL and ETL, respectively, achieving 9.9% efficient devices [110] while, Bishop et al achieved comparable device performance of 10.2% based on PSCs using spray-coated compact TiO 2 , mesoporous TiO 2 as ETLs and Spiro-OMeTAD as the HTL for their architecture. Moreover, the fabrication of 100 cm 2 large PV modules with an active area of 40 cm 2 and a PCE of up to 15.5% was realized.…”
Section: Spray Coatingmentioning
confidence: 99%
See 3 more Smart Citations